2014
DOI: 10.1021/jp502870q
|View full text |Cite
|
Sign up to set email alerts
|

Ion Jelly Conductive Properties Using Dicyanamide-Based Ionic Liquids

Abstract: The thermal behavior and transport properties of several ion jellys (IJs), a composite that results from the combination of gelatin with an ionic liquid (IL), were investigated by dielectric relaxation spectroscopy (DRS), differential scanning calorimetry (DSC), and pulsed field gradient nuclear magnetic resonance spectroscopy (PFG NMR). Four different ILs containing the dicyanamide anion were used: 1-butyl-3-methylimidazolium dicyanamide (BMIMDCA), 1-ethyl-3-methylimidazolium dicyanamide (EMIMDCA), 1-butyl-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 75 publications
2
25
1
Order By: Relevance
“…ILs can provide different physical-chemical properties and, also, change the gelatin microenvironment, being able to address one of gelatin's limitations, which concerns the entrapment of poorly water-soluble molecules [93]. The combination of ILs with gelatin is often used for the production of ion gels (IGs) [31,93,94]. This is mainly possible due to the expected set of electrostatic, hydrophobic, and H-boding interactions between the biopolymer and ILs, which lead to the formation of IGs [31].…”
Section: Gelatinmentioning
confidence: 99%
See 2 more Smart Citations
“…ILs can provide different physical-chemical properties and, also, change the gelatin microenvironment, being able to address one of gelatin's limitations, which concerns the entrapment of poorly water-soluble molecules [93]. The combination of ILs with gelatin is often used for the production of ion gels (IGs) [31,93,94]. This is mainly possible due to the expected set of electrostatic, hydrophobic, and H-boding interactions between the biopolymer and ILs, which lead to the formation of IGs [31].…”
Section: Gelatinmentioning
confidence: 99%
“…This technology allows the production of versatile and conductive gels that can be molded into different shapes using different methodologies. The produced IGs are usually simpler than the common solid polymer electrolytes and exhibit improved conductivities, which boosts its use as substitutes for the existing solid-state polyelectrolytes in energy devices [94]. Moreover, these electrolytes may often be used as printable "inks" [31,94].…”
Section: Gelatinmentioning
confidence: 99%
See 1 more Smart Citation
“…TGA is a versatile tool for studying thermal stability of materials [14]. From figure 4a it can be suggested that the TGA curve of IL beyond 200 • C show three decomposition ranges.…”
Section: Thermal Decomposition Studiesmentioning
confidence: 99%
“…These membranes were effectively employed in the separation of gases such as carbon dioxide from nitrogen [ 20 , 22 ], methane [ 21 , 22 ], and hydrogen [ 22 ], or hydrogen from nitrogen [ 22 ]. In a previous work, gelatin was used as gelling material [ 23 ], originating a material known as Ion-Jelly ® [ 24 , 25 , 26 , 27 , 28 ], which was spread over a cellulose sheet to confer support for the membrane. It was shown that these membranes can sustain up to 10 MPa of pressure difference across the membrane without significant loss of ionic liquid, while presenting permeabilities to pure gases (H 2 , N 2 , O 2 , CO 2 and CH 4 ) similar to those obtained with SILMs using the corresponding IL, although with lower ideal selectivities.…”
Section: Introductionmentioning
confidence: 99%